2021
DOI: 10.1111/jcmm.16498
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in hypoxia‐reoxygenation‐induced myocardial mitochondrial damage with exogenous methane

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Furthermore, our data suggested intracellular ROS played a critical role, since both antioxidant and ROS scavenger reduced ROS ( Figure 3 ) and abolished hypoxia-induced mitochondrial malfunction ( Figure 3 ). The pivotal role of ROS during hypoxia-induced mitochondrial malfunction was also supported by previous publications, which demonstrated that hypoxia may impair mitochondrial function through inducing oxidative stress in rat cardiomyocytes [ 28 ], human renal tubular cells [ 29 ], murine fibroblasts [ 30 ], rat cerebral neuronal glial cells [ 31 ], and primary rat hippocampal neurons [ 32 ].…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, our data suggested intracellular ROS played a critical role, since both antioxidant and ROS scavenger reduced ROS ( Figure 3 ) and abolished hypoxia-induced mitochondrial malfunction ( Figure 3 ). The pivotal role of ROS during hypoxia-induced mitochondrial malfunction was also supported by previous publications, which demonstrated that hypoxia may impair mitochondrial function through inducing oxidative stress in rat cardiomyocytes [ 28 ], human renal tubular cells [ 29 ], murine fibroblasts [ 30 ], rat cerebral neuronal glial cells [ 31 ], and primary rat hippocampal neurons [ 32 ].…”
Section: Discussionsupporting
confidence: 56%
“…Growing evidence indicates that mitochondrial function is impaired after acute A/R injury. MMP serves as a mitochondrial function marker, and MMP loss suggests abnormal mitochondrial function [ 35 ]. Figures 3(a) and 3(b) depict the significant MMP loss in the A/R group.…”
Section: Resultsmentioning
confidence: 99%
“…Inhaled CH 4 reduced cytochrome c release and preserved the mitochondrial respiratory capacity in vivo and in transient anoxia-treated cell cultures as well (Strifler et al, 2016;Jász et al, 2021). Recently, we carried out a sequential study with exogenous normoxic CH 4 in simulated IR environments using a high-resolution respirometry system to quantify the ETS responses (Jász et al, 2021). In this protocol, CH 4 treatment restricted the forward electron transfer within Complex I in control mitochondria while effectively restricting RET in postanoxic mitochondria, thus it could be concluded that interaction with Complex I occupies a key position in the protective mechanism of CH 4 against a hypoxia/reoxygenation injury (Jász et al, 2021).…”
Section: Inhaled Chmentioning
confidence: 96%
“…In this line, many studies have also explored the relationship among CH 4 actions in the context of mitochondrial biology. Inhaled CH 4 reduced cytochrome c release and preserved the mitochondrial respiratory capacity in vivo and in transient anoxia-treated cell cultures as well (Strifler et al, 2016;Jász et al, 2021). Recently, we carried out a sequential study with exogenous normoxic CH 4 in simulated IR environments using a high-resolution respirometry system to quantify the ETS responses (Jász et al, 2021).…”
Section: Inhaled Chmentioning
confidence: 99%
See 1 more Smart Citation